ANALYSIS OF METAL CONTAMINATION IN PUBLIC TRANSPORT DRIVER’S HAIR MR.X IN MEDAN LOCATION - Simanungkalit, Manna Caesy Mega; Romatua Aruan, Dyna Grace (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2024)
Lead is often referred to as lead or plumbum. Lead (Pb) is a heavy metal that can cause poisoning until it can accumulate in the human body. The process of entering Pb into the body can go through several pathways, namely through food and drink, air and penetration or penetration of the membranes or layers of the skin. Hair is one of the bioindicators of heavy metal pollution because in the hair there is a sulfhydryl group that can bind lead. This research aims to determine the lead metal content in the hair of the Mr X public transportation driver on the Medan Amplas - Medan Helvetia route in 2024. A wet destruction method validation test has been carried out for the determination of lead (Pb) levels in the hair. Wet destruction using HNO3 and HCl. The analysis of the lead content of the destruction was carried out with an Atomic Absorption Spectrophotometer (SSA). The research results show that the highest Pb Lead level in hair is 24,000 ppm with a service life of 27 years, and the lowest Pb Lead level in hair is 0,400 ppm with a working period of 3 years.